THE INHERITANCE OF ISLAMIC EDUCATION VELUES THROUGH ORAL TRADITION OF PEURATEB ANEUK IN ACEH - Nurhayati Nurhayati (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2017)
The main problem in this research was how the inheritance of Islamic education values through oral peuratebaneuk tradition in Aceh. This study aimed to analyze deeply about the inheritance of Islamic education Values through the oral tradition of peurateb aneuk in Aceh. This ethnographic research used a qualitative approach with hermeneutical methods and descriptive analysis methods. The paradigm used was phenomenology. The sources of data, in this study consist of poetry singers and poems that have been documented. Data sources in this study were collected by using purposive sampling and Snowball Sampling. Data collection techniques used were literature review, non-participant observation techniques, ethnographic interview techniques, documentation techniques, and focus groups discussion (FGD) technique. The research instrument was the researcher herself (Human Instruments). It was supported by observation guides, interview guides, data recordings, note books. The data was analyzed by a hermeneutical method and descriptive analysis method. The result of the research shows that: 1. The values of Islamic education in the poetry of anauk in Aceh are: the value of aqidah education, the value of moral education, the value of social education, the value of worship education, the value of education struggle, 2. The process of inheriting the values of Islamic education through tradition Oral peurateb aneuk in Aceh was done through a. Lane: 1). Family, 2). Through the society, 3). Through the State. B. The culprit: 1). Family members, 2). Statesman, 3). Humanist 4). Aceh Traditional Assembly (MAA). 5). The research lecturers. C. The steps (methods) used by: 1). Stated by way of establishing patients, scheduling periodically festivals, incorporating in the curriculum as local content material in schools, promoting communities to carry out the oral tradition of peuratep aneuk 2). Society by carrying out the oral tradition of peurateb aneuk in homes. Follow the race events. 3). Families carry it out when they sleep child d. The material, contained in the lyrics of peurateb aneuk include 1). Aqidah (Faith), 2). Morals, 3).Worship, 4). Struggle. E. Media, which is used to pass the values of Islamic education through the oral tradition of peukanebaneuk there are two namely 1). Traditional media 2).Modern media. 3. A strong reason for the oral tradition of peurateb aneuk is still maintained because of a. As a medium of the transformation of Islamic education values. B. As an external cultural filtering, c. Historical local community, d. Strengthening local culture, e. Strengthening of literacy. 4. The contribution of oral peurateb tradition in Aceh to contemporary Islamic education, a. Theoretical Contribution: that is 1). Objectives, 2) Educators, 3).Learners, 4).A material, 5). Method. 6). Media. The six findings of this study are called pedagogic of peurateb aneuk. B. Practical contributions are 1). For educators, parents, teachers, and society. 2). For the government, set forth in: a). Qanun education. B). The curriculum at school.Key Words: Inheritance, Islamic Education Values, Oral Tradition, Peurateb Aneuk, Aceh